Pengembangan Media Wallchart Bagan Masyarakat (Bamas) Materi Pembangunan Sosial Budaya Kelas V Sekolah Dasar - Wulandari, Rizki; Nugroho, Arya Setya (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This research is based on the results of observations and interviews at UPT SD Negeri 214 Gresik. This study aims to determine: (1) the process of developing the learning device of the Community Bagan (Bamas) Wallchart media for socio-cultural development material for grade V elementary school, (2) the validity of the Community Bagan (Bamas) Wallchart media for socio-cultural development material for grade V elementary school, and (3) student responses related to the Community Bagan (Bamas) Wallchart material for socio-cultural development for grade V elementary school. The research method used is research and development or Research Development (R&D) with the ADDIE model procedure. The results of the study indicate that the development of the Community Bagan (Bamas) Wallchart media learning device uses the ADDIE model, namely the analysis, design, development, implementation, and evaluation stages. The use of the Community Bagan (Bamas) Wallchart media that was developed has been validated by 2 experts, namely the media expert getting a percentage of 69% with feasible criteria, and the material expert getting a percentage of 76% with feasible criteria. Thus, the average obtained from the two experts is getting feasible criteria with a percentage of 72.5%. The average result of the student response questionnaire for the Wallchart Community Bagan (Bamas) media conducted comprehensively to grade V elementary school totaling 18 students was 86% and obtained very good criteria